2011
DOI: 10.4081/ejh.2011.e26
|View full text |Cite
|
Sign up to set email alerts
|

Cultured myoblasts from patients affected by myotonic dystrophy type 2 exhibit senescence-related features: ultrastructural evidence

Abstract: Myotonic dystrophy type 2 (DM2) is an autosomal dominant disorder caused by the expansion of the tetranucleotidic repeat (CCTG)n in the first intron of the Zinc Finger Protein-9 gene. In DM2 tissues, the expanded mutant transcripts accumulate in nuclear focal aggregates where splicing factors are sequestered, thus affecting mRNA processing. Interestingly, the ultrastructural alterations in the splicing machinery observed in the myonuclei of DM2 skeletal muscles are reminiscent of the nuclear changes occurring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 74 publications
(79 reference statements)
3
24
0
1
Order By: Relevance
“…1,11 , 28-34 More generally, it could be hypothesised that the accumulation/delocalization of mRNA processing factors, including MBNL1, could hamper the functionality of the whole splicing machinery and slow down the intranuclear molecular trafficking, leading to a lower metabolic activity of myonuclei, consistent with the reduced protein synthesis observed in DM1 and DM2 myoblasts, 68,69 and the misregulated protein turnover resulting in a structural imbalance between protein synthesis and degradation in aged muscles 70 . It is worth noting that myoblasts from DM2 patients grown in culture show cell-senescence structural alterations and impairment of the pre-mRNA maturation pathways much earlier than the myoblasts from healthy subjects 71 . The skeletal muscle of DM patients seems therefore to share intriguing similarities with the muscle from aged mammals, with special reference to the alterations in the nuclear RNP-containing structures involved in pre-mRNA transcription and splicing.…”
Section: Discussionsupporting
confidence: 71%
“…1,11 , 28-34 More generally, it could be hypothesised that the accumulation/delocalization of mRNA processing factors, including MBNL1, could hamper the functionality of the whole splicing machinery and slow down the intranuclear molecular trafficking, leading to a lower metabolic activity of myonuclei, consistent with the reduced protein synthesis observed in DM1 and DM2 myoblasts, 68,69 and the misregulated protein turnover resulting in a structural imbalance between protein synthesis and degradation in aged muscles 70 . It is worth noting that myoblasts from DM2 patients grown in culture show cell-senescence structural alterations and impairment of the pre-mRNA maturation pathways much earlier than the myoblasts from healthy subjects 71 . The skeletal muscle of DM patients seems therefore to share intriguing similarities with the muscle from aged mammals, with special reference to the alterations in the nuclear RNP-containing structures involved in pre-mRNA transcription and splicing.…”
Section: Discussionsupporting
confidence: 71%
“…However, in vitro primary myoblasts obtained from muscle of adult DM patients do not show evident morphological abnormalities and are capable of normally differentiating [74, 102, 103]. Conversely, recent data demonstrated that DM2 myoblasts are characterized by senescence related features mainly consisting in the early appearance of cytological alterations and impairment of the pre-mRNA maturation pathways [104]. Moreover, Renna et al [105] reported that DM1 and DM2 myoblasts are characterized by a premature proliferative growth arrest compared to healthy myoblasts through a mechanism similar to senescence since both DM1 and DM2 cells expressed biomarkers usually observed in senescent cells.…”
Section: Myotonic Dystrophy Typementioning
confidence: 99%
“…Myoblast cell therapy can be also potentially offered to dystrophic patients. It is well documented that muscular dystrophies are frequently linked to premature cell aging and exhaustion of satellite cells pool [24] so dystrophic myoblasts obtained from relatively young individuals should be considered as the adult ones demonstrating of diminished proliferative potential.…”
Section: Discussionmentioning
confidence: 99%